2020
DOI: 10.1371/journal.pone.0226917
|View full text |Cite
|
Sign up to set email alerts
|

The role of survivin in the progression of pancreatic ductal adenocarcinoma (PDAC) and a novel survivin-targeted therapeutic for PDAC

Abstract: Treating pancreatic ductal adenocarcinoma (PDAC) remains a major hurdle in the field of oncology. Less than half of patients respond to frontline chemotherapy and the pancreatic tumor microenvironment limits the efficacy of immunotherapeutic approaches. Targeted therapies could serve as effective treatments to enhance the clinical response rate. One potential therapeutic target is survivin, a protein that is normally expressed during embryonic and fetal development and has a critical impact on cell cycle contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…In a study on the anticancer properties of FZD7 after pharmacological inhibition of HCC, it was suggested that the mechanism may be associated with PRKCD mutations (32). BIRC5 has been described as a negative regulator of apoptosis, and its expression was reported to be higher in most tumors including HCC (33)(34)(35)(36), which is consistent with our findings indicating that the expression of BIRC5 is higher in the high-risk group of HCC prognosis. Moreover, the potential influence of BIRC5, HMOX1, and VEGFA in the prognosis of HCC had been reported in studies by Wang et al(37), Shen et al (38), and…”
Section: Discussionsupporting
confidence: 91%
“…In a study on the anticancer properties of FZD7 after pharmacological inhibition of HCC, it was suggested that the mechanism may be associated with PRKCD mutations (32). BIRC5 has been described as a negative regulator of apoptosis, and its expression was reported to be higher in most tumors including HCC (33)(34)(35)(36), which is consistent with our findings indicating that the expression of BIRC5 is higher in the high-risk group of HCC prognosis. Moreover, the potential influence of BIRC5, HMOX1, and VEGFA in the prognosis of HCC had been reported in studies by Wang et al(37), Shen et al (38), and…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, we provide evidence that the anti-tumor effects observed after SLFN5 depletion are mediated, at least in part, by interfering with cell cycle progression. This is important, as PDAC tumors are characterized by the presence of cell cycle dysregulation, a hallmark of several types of cancer, 36 , 37 and the identification of SLFN5 as a new promoting factor of S phase progression may help expand the currently available armory of cell cycle inhibitors 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Survivin Survivin is physiologically expressed during embryonic and fetal development and plays a critical role in cell cycle control and apoptosis. In PDAC it is re-expressed in about 80% of patients [202], with elevated expression associated with worse prognosis and treatment resistance [203]. Shima et al [178,179] utilized a survivin 2B-vaccine (SVN-2B) in a phase 2 clinical trial with randomization design in which 83 advanced PDAC patients were included, all pre-treated with at least one line of chemotherapy.…”
Section: Vegfrmentioning
confidence: 99%